Lessons from a Single Amino Acid Substitution: Anticancerand Antibacterial Properties of Two PhospholipaseA2-Derived Peptides - de Almeida, José R. (2021)
The membrane-active nature of phospholipase A2-derived peptides makes them potentialcandidates for antineoplastic and antibacterial therapies. Two short 13-mer C-terminal fragmentstaken from snake venom Lys49-PLA2toxins (p-AppK and p-Acl), differing by a leucine/phenylalaninesubstitution, were synthesized and their bioactivity was evaluated. Their capacity to interfere withthe survival of Gram-positive and Gram-negative bacteria as well as with solid and liquid tumorswas assessedin vitro. Toxicity to red blood cells was investigated via in silico andin vitrotechniques.The mode of action was mainly studied by molecular dynamics simulations and membrane permeabi-lization assays. Briefly, both peptides have dual activity, i.e., they act against both bacteria, includingmultidrug-resistant strains and tumor cells. All tested bacteria were susceptible to both peptides,Pseudomonas aeruginosabeing the most affected. RAMOS, K562, NB4, and CEM cells were the mainleukemic targets of the peptides. In general, p-Acl showed more significant activity, suggestingthat phenylalanine confers advantages to the antibacterial and antitumor mechanism, particularlyfor osteosarcoma lines (HOS and MG63). Peptide-based treatment increased the uptake of a DNA-intercalating dye by bacteria, suggesting membrane damage. Indeed, p-AppK and p-Acl did notdisrupt erythrocyte membranes, in agreement with in silico predictions. The latter revealed that thepeptides deform the membrane and increase its permeability by facilitating solvent penetration. Thisphenomenon is expected to catalyze the permeation of solutes that otherwise could not cross thehydrophobic membrane core. In conclusion, the present study highlights the role of a single aminoacid substitution present in natural sequences towards the development of dual-action agents. Inother words, dissecting and fine-tuning biomembrane remodeling proteins, such as snake venomphospholipase A2isoforms, is again demonstrated as a valuable source of therapeutic peptides.